Oxygen Precipitation in Highly Doped Silicon Substrates. (1st January 2019) - Porrini, M.; Voronkov, V. V.; Giannattasio, A.
Abstract : This paper reviews oxygen precipitation in heavily arsenic-doped silicon. A wide arsenic concentration range is explored, from 3 × 10 18 cm −3 to 4 × 10 19 cm −3 . A precipitation retardation effect is observed in the arsenic doped samples when the dopant concentration is higher than 1.7 × 10 19 cm −3 compared with lightly doped samples having the same initial oxygen content and grown under similar conditions. The oxygen precipitate density in the heavily arsenic-doped samples is uniform along the wafer radius, with no rings or cores, contrary to what is commonly observed in lightly doped samples grown with similar V/G values. This finding is discussed by considering the role played by vacancies in the formation of oxygen precipitates and the impact of the arsenic concentration on the equilibrium concentration of point defects in silicon, deduced from the experimentally observed voids revealed as light-scattering surface defects in polished wafers.